Improvement of Shoulder Motion in Two-Stage Dual-Plane Implant-Based Breast Reconstruction followed by Radiation Therapy through Delayed Prepectoral Conversion - Park, Jin Sol; Jin, Ung Sik (Archives of Plastic Surgery, 2024)
Background Although prepectoral implant-based breast reconstruction has recently gained popularity, dual-plane reconstruction is still a better option for patients with poor-quality mastectomy skin flaps. However, shoulder morbidity is aggravated by subpectoral reconstruction, especially in irradiated patients. This study aimed to demonstrate shoulder exercise improvement in subpectoral reconstruction by delayed prepectoral conversion with an acellular dermal matrix (ADM) inlay graft technique at the time of expander-to-implant exchange after irradiation.Methods Patients with breast cancer treated for expander-to-implant exchange after subpectoral expander insertion and subsequent radiotherapy between January 2021 and June 2022 were enrolled. An ADM inlay graft was inserted between the pectoralis major muscle and the previously inserted ADM. The ADM was sutured partially overlapping the pectoralis muscle from the medial side with the transition part, to the muscle border at the lateral side. Perioperative shoulder joint active range-of-motion (ROM) for forward flexion, abduction, and external rotation was also evaluated.Results A total of 35 patients were enrolled in the study. Active shoulder ROM significantly improved from 163 degrees preoperatively to 176 degrees postoperatively in forward flexion, 153 to 175 degrees in abduction, and 69 to 84 degrees in external rotation. There was no difference in patient satisfaction regarding the final outcome between the conventional prepectoral reconstruction group and the study group.Conclusion Shoulder exercises in irradiated patients who underwent subpectoral reconstruction were improved by delayed prepectoral conversion using an ADM inlay graft. It is recommended that subpectoral reconstruction not be ruled out due to concerns regarding muscle contracture and shoulder morbidity in radiation-planned patients with poor mastectomy skin flaps.
Keywords: breast reconstruction; acellular dermal matrix; radiotherapy; shoulder